Implementasi Prosedur Audit Aset Tetap: Studi Kasus pada PT X oleh KAP XYZ - Bilqis Agustina Windiary; Endah Susilowati (Jurnal Riset Manajemen dan Akuntansi, 2026)
This study aims to describe the implementation of fixed asset audits at PT X by Public Accounting Firm XYZ. The study uses a qualitative approach with descriptive methods and data collection techniques used are direct observation and interviews with auditors involved in the audit process. The audit procedures carried out include requests for fixed asset data, preparation of working papers, vouching, depreciation recalculation, verification of asset disposal, and evaluation of financial statement presentation. The results of the study indicate that the audit was carried out systematically and efficiently, although there were certain problems such as incomplete documentation and a manual inventory system. The auditor successfully adjusted the audit approach to the conditions in the field and concluded that there was no material misstatement in the fixed asset accounts of PT X.